'Not on the radar': dentists' perspectives on the oral health care of dependent older people. (16th May 2016) - Smith, Moira B.; Thomson, William Murray
Abstract : Objectives: We explored the following research questions: (i) what challenges do dentists face when providing oral health care to dependent older adults; and (ii) to overcome those challenges, what recommendations would dentists providing care give those planning and implementing oral health policy and services for dependent older adults? Background: The dentate older population is steadily increasing, and about half will end up in residential care, where dental caries rates over time are at least twice as great as those observed elsewhere. Materials and methods: A qualitative study was used, with semi‐structured interviews conducted by a single interviewer. Dental examiners in a recent national survey of oral health in dependent older people in New Zealand were interviewed about their experiences and perspectives of that. Results: The challenges participants identified stemmed from three areas – the patient, the care facility and the oral health sector. To address those challenges, the participants recommended actions at the patient, system and sector levels. Each of the challenges and recommendations had a number of subthemes. Overall, the dentists felt that it is a very complex situation urgently requiring policy development, cross‐sectoral collaboration and upskilling of the dental profession, carers, the private sector and the State to ensure a care environment which supports achieving and maintaining oral health among frail elders. Conclusions: Urgent attention to frail older New Zealanders' oral health is needed. Such attention needs to focus on not only the narrow dental clinical preventive and therapeutic implications of those needs, but also on the broader health system and policy development challenges.